Five Myths About eXtension - Terry Meisenbach; Lynette Spicer (Journal of Applied Communications, 2007)
eXtension has finally launched, and more and more Cooperative Extension faculty and staff are becoming involved. However, there are still a few rumors and myths that need to be dispelled. We hope that we can clear up the confusion and open the door to your participation as we transform Cooperative Extension for the future.